EVALUATION OF THE DEVELOPMENT STRATEGY OF THE STIEIMA SMALL BUSINESS INCUBATOR BASED ON THE IDENTIFICATION OF INTERNAL AND EXTERNAL FACTORS - Wea, Maria Angelia; Novaretha , Adinda Yosa; Mahdi, Ahmad Syakban Alfian; Aini, Alvia Nur; Putri, Amanda Olivia; Hariyanto, Bintang Cahya; B.S.M, Dama Rio Laksamana; Putri, Fira Desika; P.S, Icha Sukma; Maulana, Ifan Rachmad; Setyawati, Amelia (Nusantara Economics and Entrepreneurships Journals, 2025)
This study aims to evaluate the development strategy of STIEIMA's Small Business Incubator (SBI) by identifying internal and external factors that influence its performance. STIEIMA's SBI serves as a forum for fostering student entrepreneurship by providing production support, mentoring, operational facilities, and marketing access. The research uses a qualitative descriptive approach with data collection techniques in the form of field observations, interviews with managers, and documentation of operational activities. The results of the analysis show that the main internal strengths include ownership of production and brands, as well as low-cost supplier relationships. Meanwhile, significant weaknesses include an unstrategic location, limited facilities, short operating hours, and the risk of defective products. External factors indicate opportunities in the form of marketing digitalization and online store development, as well as the potential for collaboration with surrounding MSMEs. On the other hand, threats come from business competition around the campus and increasingly competitive online sellers. Based on the SWOT analysis, SBI STIEIMA is in a position that requires a development strategy through product diversification, digital marketing optimization, facility improvements, and strengthened operational management. This study emphasizes that the formulation of an appropriate strategy based on internal and external factors is necessary to enhance the competitiveness and sustainability of the incubation program in the campus environment.